NEW OPPORTUNITIES FOR LEARNING FOREIGN LANGUAGES IN UZBEKISTAN - Babajanova, Dilorom (Current Research Journal of History, 2021)
The article analyzes the introduction of teaching foreign languages in Uzbekistan, the processes associated with new opportunities for teaching languages, as well as the problems of training specialists in foreign languages on the basis of archival data and government decisions.